Positive interpretation bias predicts well-being in medical interns - Kleim, Birgit; Thörn, Hanna A.; Ehlert, Ulrike (Frontiers in Psychology, 2014)
Cognitive theories of emotion posit that affective responses may be shaped by how individuals interpret emotion-eliciting situations. This study tested whether individual differences in interpretation bias (i.e., interpreting ambiguous scenarios in a more negative or positive manner) independently predicted trait resilience and depression in medical interns. Interpretation bias and trait resilience scores were assessed in 47 interns prior to their first internship. Depressive symptoms were assessed twice during internship. Nearly half of the sample (42%) scored above the cut-off for mild depressive symptoms during internship, a significant rise compared to the initial assessment. Those with a more positive interpretation bias had higher trait resilience (β= .44, p= .004) and a 6-fold decreased depressive symptom risk during internship (OR= 6.41, p= .027). The predictive power of the interpretation bias for depression symptoms held over and above initial depressive symptoms, demographics and trait reappraisal. Assessing positive interpretation bias may have practical utility for predicting future well-being in at risk-populations.